2014
DOI: 10.1614/ws-d-13-00169.1
|View full text |Cite
|
Sign up to set email alerts
|

Alleles Contributing to ACCase-Resistance in an Italian Ryegrass (Lolium perennessp.multiflorum) Population from Oregon

Abstract: Acetyl-coenzyme A carboxylase (ACCase)–resistant Italian ryegrass is one of the most difficult-to-control weeds in United States wheat-production systems. Seed was collected from a suspected ACCase-resistant Italian ryegrass population in a winter wheat field with a history of ACCase-inhibitor herbicide use. This study investigated cross-resistance patterns in this Italian ryegrass population. Resistance was identified to the commercial dose of the ACCase herbicides pinoxaden, clethodim, sethoxydim, and clodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…Further studies are needed to verify this, since the same population could harbor individuals with different point mutations conferring resistance to ACCase herbicides from different groups, or individual plants could carry two different mutant sites that endow resistance to more than one ACCase herbicide group. Also, populations from different geographical areas could harbor different mutations (Yu et al, 2007;Liu et al, 2007;Cruz-Hipolito et al, 2011;Délye et al, 2010;Gherekhloo et al, 2012;Marshall et al, 2013;Li et al, 2013Li et al, , 2014Malone et al, 2014;Martins et al, 2014). In addition, the level of resistance depends on the number of resistant alleles in individual plants (Cha et al, 2014;Martins et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies are needed to verify this, since the same population could harbor individuals with different point mutations conferring resistance to ACCase herbicides from different groups, or individual plants could carry two different mutant sites that endow resistance to more than one ACCase herbicide group. Also, populations from different geographical areas could harbor different mutations (Yu et al, 2007;Liu et al, 2007;Cruz-Hipolito et al, 2011;Délye et al, 2010;Gherekhloo et al, 2012;Marshall et al, 2013;Li et al, 2013Li et al, , 2014Malone et al, 2014;Martins et al, 2014). In addition, the level of resistance depends on the number of resistant alleles in individual plants (Cha et al, 2014;Martins et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Also, populations from different geographical areas could harbor different mutations (Yu et al, 2007;Liu et al, 2007;Cruz-Hipolito et al, 2011;Délye et al, 2010;Gherekhloo et al, 2012;Marshall et al, 2013;Li et al, 2013Li et al, , 2014Malone et al, 2014;Martins et al, 2014). In addition, the level of resistance depends on the number of resistant alleles in individual plants (Cha et al, 2014;Martins et al, 2014). Cha et al (2014) have demonstrated that an E. indica biotype containing homozygous 2027-Cys allele could endow a higher level of resistance to fluazifop-P-butyl than a mix (heterozygous) Trp-and Cys-2027 allele biotype.…”
Section: Resultsmentioning
confidence: 99%
“…Tehranchian et al (2017) documented presence of an I1781L in two resistant biotypes from California . In an ACCase inhibitor‐resistant Italian ryegrass population from Oregon, two mutations, I2041N and D2078G, were found . A population from the UK, RG3, had a C2088R mutation …”
Section: Discussionmentioning
confidence: 99%
“…Aryloxyphenoxypropionate (APP) and cyclohexanedione (CHD) herbicides are potent inhibitors of acetyl coenzyme A carboxylase (ACCase; EC 6.4.1.2) and are commonly used for the control of various grass weeds. Resistance to ACCase‐inhibiting herbicides in most cases has been attributed to insensitivity of the target enzyme . However, metabolism‐based resistance to ACCase inhibitors has been identified in a comparatively small number of weed species .…”
Section: Introductionmentioning
confidence: 99%